(untitled) (Journal of Informatics and Mathematical Sciences, 2022)
This paper deals with the motion of oblate infinitesimal mass around the triaxial primaries in the framework of elliptical restricted three body problem. The triaxial primaries are moving around each other in elliptic orbits about the common barycentre and the oblate infinitesimal is moving in the neighbourhood of collinear equilibrium points. It is observed that location and stability of the oblate infinitesimal around the collinear points are affected by the triaxiality of primaries. Furthermore, the results shown that the behaviour of infinitesimal mass around the collinear points \(L_1\) and \(L_2\) are unstable, while the behaviour of infinitesimal mass around \(L_3\) is shown stable for some parameters of triaxiality of primaries.